Perbedaan Kualitas Hidup antara Terapi Hemodialisis dengan Terapi Continuous Ambulatory Peritoneal Dialysis (CAPD) pada Pasien Gagal Ginjal Kronik - Musnelina, Lili; Kurniati, Ditha; Ferdinal, Del (LPPM, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2023)
Chronic Kidney Disease (CKD) is a progressive and irreversible disorder of kidney function. CKD patients who enter the final stage must immediately get renal replacement therapy to maintain their life. The most widely used kidney replacement therapy hemodialysis (HD) and peritonial dialysis (CAPD). Therapies performed either HD or CAPD cause various side effects such as physical fatigue, impaired concentration, disruption of social life and risk of infection. Side effects affect the quality of life of CKD patients. The purpose of this study was to the determine the differences quality of life chronic kidney failure patients between HD and CAPD. This research was an analytic observational research using the SF- 36 questionnaire. The results have shown that the average value of quality of life was significally different, the average score in the CAPD therapy group was 71.06 ± 13.92 and the HD therapy group the average score was 48.08 ± 14.37. The study found a that the majority of the CAPD therapy group have a good quality of life than the HD therapy group.